A bonding anode carbon block and a safe bonding method thereof

By combining the design of the cube structure and the filling block slider, the rapid bonding and stable connection of the anode carbon block are achieved, solving the problems of low bonding efficiency and safety risks in the prior art, and improving electrolytic stability and safety.

CN118621383BActive Publication Date: 2025-01-03CHIPING HUAXU NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411019527.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-03
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

In the prior art, the bonding efficiency of the anode carbon block is low and requires a large-scale polishing treatment, which leads to wasted time and unstable bonding. It is easy to generate impurities during the bonding process to affect the electrolyte, increasing safety risks.

Method used

A bonded anode carbon block is designed, adopting a cube structure, with plug-in grooves, grooves and limit blocks on the side walls. Through the cooperation of the filling block and the slider, the rapid bonding and stable connection of the anode carbon block is achieved. , reduce the use of grinding and mud, and improve bonding efficiency and safety.

Benefits of technology

Through physical coordination, the fast bonding and stability of the anode carbon block is improved, the grinding time is reduced, the generation of impurities is reduced, the electrolytic stability and safety is improved, and the impact of mud use and impurities in the electrolytic tank is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118621383B_ABST
    Figure CN118621383B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of aluminum electrolysis, and in particular to a bonding anode carbon block and a safe bonding method thereof, which includes: a carbon block substrate, which is arranged in a cubic shape, with a first plug-in slot provided on the side wall, and grooves provided on the side walls on both sides of the first plug-in slot; a protrusion, which is arranged on the side wall of the carbon block substrate away from the first plug-in slot, and has a connecting slot to form a carbon bowl, and can be plugged into the first plug-in slot of an adjacent anode carbon block; a limiting block, which is arranged on the side wall of the carbon block substrate away from the protrusion, and is provided with two, respectively located on both sides of the first plug-in slot, and a hooking portion is formed on the side walls of the two limiting blocks close to each other, and the hooking portion can be hooked into the groove; a filling block, which matches the shape of the connecting slot and is used to fill the carbon bowl during bonding. The present application has the effect of improving bonding efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aluminum electrolysis, and in particular to a bonded anode carbon block and a safe bonding method thereof. Background Art

[0002] At present, modern electrolytic aluminum industry uses prebaked anodes to produce electrolytic aluminum. Usually, prebaked anode carbon blocks are used intermittently, and the service life of an anode carbon block is about 30 days. Prebaked anode carbon blocks are gradually consumed during use. When the remaining height is 15-18 cm, they must be removed from the electrolytic cell and replaced with new anode carbon blocks. Prebaked anodes are generally rectangular with a stable geometric shape. They are formed by evenly mixing rock tar and asphalt coke as aggregates and coal tar or phenolic resin as binders in a mold.

[0003] In the prior art, a Chinese patent with authorization announcement number CN109913905B discloses a method for bonding continuous prebaked anode carbon blocks. When the thickness of the anode carbon block used in the electrolytic cell is 250 to 300 mm, an old anode carbon block is obtained. The upper surface of the old anode carbon block is first cooled, and the pre-coated foam mud on the upper surface of the old anode carbon block that has been sintered and hardened is roughened. Then, the foam mud is applied on the lower surface of the new anode carbon block, and the new anode carbon block is stacked up and down with the old anode carbon block, and squeezed and bonded together. However, there are protrusions on the upper surface of the existing anode carbon block, and a carbon bowl for connecting the anode steel claw is provided on the protrusion. It is time-consuming to machine and grind the upper surface of the old anode carbon block to make it smooth, which leads to a decrease in bonding efficiency. Summary of the invention

[0004] In order to improve the bonding efficiency, the present application provides a bonded anode carbon block and a safe bonding method thereof.

[0005] In the first aspect, the present application provides a bonded anode carbon block, which adopts the following technical solution:

[0006] A bonded anode carbon block, comprising:

[0007] The carbon block substrate is in a cubic shape, with a first inserting groove formed on the side wall, and grooves formed on the side walls on both sides of the first inserting groove;

[0008] A protrusion is arranged on the side wall of the carbon block substrate away from the first plug-in groove, and is provided with a connecting groove to form a carbon bowl, and can be plugged into the first plug-in groove of another anode carbon block;

[0009] A limit block is arranged on the side wall of the carbon block substrate away from the protrusion, and two limit blocks are arranged, respectively located on both sides of the first plug-in slot, and hooking parts are formed on the side walls of the two limit blocks close to each other, and the hooking parts can be hooked in the groove of another anode carbon block;

[0010] The filling block matches the shape of the connecting groove and is used to fill the carbon bowl during bonding.

[0011] By adopting the above technical scheme, the anode steel claw is connected to the carbon bowl through phosphorus pig iron or mechanical connection, and then the anode carbon block is extended into the electrolytic cell for electrolysis. The groove setting and the first plug-in slot are used to facilitate exhaust and improve the stability of electrolysis. When the anode carbon block is consumed and the length is shortened to 250-300 mm, an old anode carbon block is obtained, and then the old anode carbon block is cooled. After cooling, the new anode carbon block is taken out and the surface is cleaned. Then the filling block is placed in the carbon bowl of the cooled old anode carbon block, and then the new anode carbon block is heated to expand the new anode carbon block. Then, foam mud or molten raw materials of the carbon block are coated in the first plug-in slot of the heated new anode carbon block. Then, the new anode carbon block and the old anode carbon block are abutted so that the protrusion of the old anode carbon block is plugged into the first plug-in slot of the new anode carbon block. The hooking portion formed by the first limiting block is hooked with the groove of the old anode carbon block, and then naturally cooled and then sintered, or directly sintered, so that the foam mud is solidified. The solidified foam mud has better conductivity and can be electrolyzed normally; through the above-mentioned arrangement, large-scale grinding and cleaning can be reduced, and the bonding efficiency is improved, and the connection between the two does not only rely on the bonding of the foam mud, but also improves the speed and stability of the connection through physical cooperation; when splicing, only the surface cleaning is required, and the connection stability is high. During sintering, there is no need to squeeze the new anode carbon block and the old anode carbon block all the time, which can make the foam mud bond stably to the anode carbon block and the cathode carbon block, and can reduce the use of foam mud, reduce the excessive doping of impurities that are difficult to electrolyze in the electrolytic cell, and reduce the impact on electrolysis; and reduce the unstable bonding, falling into the electrolytic cell, disturbing the electrolyte, reducing safety risks, and improving safety.

[0012] Optionally, a filling hole is opened on the side wall of the carbon block substrate, and the filling hole is connected to the first plug-in groove and corresponds to the connecting groove.

[0013] By adopting the above technical scheme, the extrusion of foam mud is facilitated by the setting of the filling hole. At the same time, foam mud or molten carbon block raw materials can be filled into the carbon bowl and the first plug-in slot through the filling hole, thereby reducing the bonding gap and improving the bonding stability between the new anode carbon block and the old anode carbon block, making the filling denser and reducing the impact on electrolysis. The infusion is fast and can be completed quickly, thereby improving the bonding efficiency and reducing the rework caused by the separation of the two.

[0014] Optionally, a rotating groove is provided in the connecting groove, and the rotating groove is spirally provided along the axis of the connecting groove; a second plug-in groove is provided at the bottom of the first plug-in groove, a sliding groove is provided on the side wall of the second plug-in groove, and an annular groove is provided at the bottom of the second plug-in groove, and the sliding groove is connected with the annular groove; a sliding block is provided on the filling block, and the sliding block slides along the sliding groove and enters the annular groove.

[0015] By adopting the above technical scheme, firstly, the foam mud is filled in the slide groove, the second plug-in groove and the carbon bowl, and then the end of the filling block with the slider is inserted into the slide groove, the slider is moved to the annular groove, and then the new anode carbon block is close to the old anode carbon block. As the two get closer, one end of the filling block is inserted into the rotating groove, and as the rotating groove rotates, the slider slides and rotates in the annular groove to fix the filling block, and then the hook portion is hooked with the groove, and then extrusion is performed, and then filling is performed through the filling hole, and then extrusion is performed, and finally sintering is performed. Through the above arrangement, the connection between the two is more stable, and during sintering, no external force is required, and the connection seam between the two is filled more densely; and through the opening of the above grooves and holes, when a complete anode carbon block is used alone for electrolysis, gas discharge can be facilitated, the electrolyte is more stable, and the current distribution is convenient, reducing energy consumption.

[0016] Optionally, a first locking groove is formed on the side wall of the limit block, the first locking groove is communicated with the groove, and a second locking groove is formed on the groove, and a locking rod is inserted into both the first locking groove and the second locking groove.

[0017] By adopting the above technical solution, through the setting of the first locking groove and the second locking groove, the old anode carbon block and the new anode carbon block are fixed by the locking rod, so as to improve the stability of the connection between the two and reduce the gap separation between the two, so that the foam mud between the two maintains a certain thickness, reduces expansion during sintering, and improves the connection stability.

[0018] In the second aspect, the present application provides a method for safely bonding a bonded anode carbon block, which adopts the following technical solution:

[0019] A method for safely bonding anode carbon blocks, comprising the following steps:

[0020] Cleaning: clean the protrusions of the old anode carbon block, clean the carbon bowl, and clean the grooves;

[0021] Bonding preparation: Apply foam mud on the raised surface of the old anode carbon block, pour foam mud into the second insertion groove and the slide groove of the new anode carbon block, and then insert the filling block and the slider into the second insertion groove and the slide groove of the new anode carbon block respectively;

[0022] Seam treatment: plug the first plug-in groove of the new anode carbon block into the protrusion of the old anode carbon block, and hook the hook part of the limit block of the new anode carbon block into the groove of the old anode carbon block;

[0023] Seam pressing treatment: squeeze the old anode carbon block and the new anode carbon block close to each other to make them bond;

[0024] Sintering treatment: Sinter the connected new anode carbon blocks and old anode carbon blocks to form a stable structure.

[0025] By adopting the above technical scheme, when bonding the old anode carbon block and the new anode carbon block, first the surface of the old anode carbon block is cleaned, the debris in the carbon bowl is taken out, the groove is cleaned or the groove is opened, and then the surface of the old anode carbon block is smeared with foam mud, a small amount of foam mud is filled in the second plug-in slot and the slide slot, and then the filling block and the slider are respectively inserted in the second plug-in slot and the slide slot, and then the new anode carbon block is brought close to the old anode carbon block and close to each other, so that the filling block slides and rotates in the carbon bowl, and the two are bonded and fixed, and then sintering is performed to solidify the foam mud and bond the old anode carbon block and the new anode carbon block; through the above process, on the one hand, unnecessary grinding is reduced, time waste is reduced, and bonding efficiency is improved; on the other hand, the waste of carbon blocks is reduced; on the other hand, the large amount of foam mud used can be reduced to affect electrolysis; on the other hand, the connection between the old anode carbon block and the new anode carbon block is more stable, which can reduce the separation between the two, or unilateral tilting expansion, so that the electrolysis characteristics can be maintained.

[0026] Optionally, a cold and hot treatment step is provided before the bonding preparation step;

[0027] Hot and cold treatment: cool the old anode carbon block and then preheat the new anode carbon block to make it expand.

[0028] By adopting the above technical scheme, during splicing, the old anode carbon block is cooled and the new anode carbon block is preheated, so that the new anode carbon block can expand, which is convenient for the new anode carbon block to be mounted on the old anode carbon block, and the two can be interference fit, which can reduce the separation between the two during sintering, and restrict each other with the filling block slider to improve the connection stability between the two, and preheat the new anode carbon block, so that when electrolysis is officially carried out, the new anode carbon block can quickly adapt to the electrolysis temperature and respond to electrolysis quickly.

[0029] Optionally, after the seam-aligning step, a seam-filling step is further provided;

[0030] Seam filling treatment: fill the connection groove and the first plug-in groove with foam mud or anode carbon block mixed raw materials through the filling hole.

[0031] By adopting the above technical solution, after the seaming is completed, the foam mud or carbon block mixed raw material is filled into the first plug-in slot through the filling hole, which facilitates the filling of the interior and reduces the generation of internal gaps, making the bonding between the two more firm and forming a dense bonding layer, thereby reducing the impact on exhaust during electrolysis and maintaining the electrolysis efficiency.

[0032] Optionally, in the cold and hot treatment steps, the temperature difference between the new anode carbon block and the old anode carbon block is controlled at 200°C-250°C.

[0033] By adopting the above technical solution, the temperature difference between the two is maintained at 200℃-250℃, which can reduce the excessive temperature difference between the two and the shear force generated, and heat conduction is carried out between the two, which is convenient for the initial solidification of the foam mud, improves the bonding efficiency, reduces the flow of the foam mud, shortens the sintering heating time, quickly completes the bonding, and improves the bonding efficiency.

[0034] Optionally, after the seam pressing step, a pre-heating step is further provided;

[0035] Pre-heating treatment: Use a clamp to squeeze the two ends of the connection seam between the old anode carbon block and the new anode carbon block, and then pre-heat the temperature so that the temperature difference between the new anode carbon block and the old anode carbon block is less than 30℃-50℃.

[0036] By adopting the above technical scheme, after the seam pressing treatment is completed, the temperature between the new anode carbon block and the old anode carbon block is balanced by pre-heating, reducing the high temperature difference between the two, and the foam mud on the outer edge is restrained by the setting of the splint, so that the foam mud is initially solidified, reducing the flow of the side foam mud, forming protrusions or pits, making the surface of the anode carbon block uneven, affecting the electrolysis.

[0037] Optionally, in the bonding preparation step, when the foam mud is applied to the surface of the old anode carbon block, the surface is heated, and gradient heating is adopted during heating to gradually reduce the temperature from the protruding position of the old anode carbon block toward the outer edge.

[0038] By adopting the above technical scheme, when the foam mud is coated, the expansion of the groove is reduced by step-by-step heating, and the excessive temperature difference on the surface of the old anode carbon block is reduced. The adhesion of the foam mud can be improved by heating, so that the foam mud can deeply penetrate into the gaps on the surface of the old anode carbon block, thereby improving the bonding performance and maintaining the conductive performance.

[0039] In summary, the present application includes at least one of the following beneficial technical effects:

[0040] 1. Reduce large-scale grinding and cleaning, improve bonding efficiency, and the connection between the two does not only rely on the bonding of foam mud, but also improves the speed and stability of connection through physical coordination; when splicing, only the surface cleaning is required, and the connection stability is high. During sintering, there is no need to squeeze the new anode carbon block and the old anode carbon block all the time, which can make the foam mud bond the anode carbon block and the cathode carbon block stably, and can reduce the use of foam mud, reduce the excessive impurities that are not easy to electrolyze in the electrolytic cell, and reduce the impact on electrolysis;

[0041] 2. On the one hand, it reduces unnecessary grinding, reduces time waste, and facilitates improving bonding efficiency. On the other hand, it reduces the waste of carbon blocks. On the other hand, it can reduce the large-scale use of foam mud that affects electrolysis. On the other hand, the connection between the old anode carbon block and the new anode carbon block is more stable, which can reduce the separation between the two, or unilateral tilt expansion, so that the electrolysis characteristics can be maintained;

[0042] 3. After the seam is aligned, fill the first plug-in slot with foam mud or carbon block mixed raw materials through the filling hole to facilitate filling the interior and reduce the generation of internal gaps, making the bonding between the two more firm and forming a dense bonding layer, reducing the impact on exhaust during electrolysis and maintaining the electrolysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a schematic diagram of the connection between the new and old anode carbon blocks in the embodiment of the present application;

[0044] Figure 2 is a cross-sectional view of an anode carbon block according to an embodiment of the present application;

[0045] Figure 3 for Figure 2 A magnified view of middle;

[0046] Figure 4 This is a diagram showing the first insertion slot of the anode carbon block.

[0047] Attached to the drawing are numerals: 100, carbon block substrate; 110, first plug-in slot; 120, groove; 130, filling hole; 140, second plug-in slot; 150, slide slot; 160, annular groove; 200, protrusion; 210, carbon bowl; 211, connecting slot; 212, rotating slot; 300, limiting block; 310, hooking portion; 320, first locking slot; 400, filling block; 500, slider; 600, rotating block; 700, locking rod. DETAILED DESCRIPTION

[0048] The following combination Figures 1 to 4 This application is described in further detail.

[0049] This embodiment discloses a bonded anode carbon block.

[0050] Reference Figures 1 to 4 The adhesive anode carbon block comprises: a carbon block substrate 100, a protrusion 200 integrally arranged on the carbon block substrate 100, a limiting block 300 on the carbon block substrate 100 for clamping adjacent carbon block substrates 100, and a filling block 400 arranged on the protrusion 200 for connecting adjacent carbon block substrates 100. When bonding the old anode carbon blocks, first clean the surfaces of the two, then apply foam mud on the surfaces, and then bring the two close to each other so that the filling block 400 connects the two, and the limiting block 300 is clamped with the adjacent carbon block substrate 100.

[0051] The carbon block substrate 100 is arranged in a cubic structure, and the protrusion 200 is arranged on one side along the length direction of the carbon block substrate 100. The vertical section of the protrusion 200 is an isosceles trapezoid, and the protrusion 200 is located in the middle of the width direction of the carbon block substrate 100. A connecting groove 211 is opened on the protrusion 200, and a rotating groove 212 is opened on the inner wall of the connecting groove 211. The rotating groove 212 is spirally arranged and rotates along the axis of the connecting groove 211. The connecting groove 211 and the rotating groove 212 form a carbon bowl 210; a first plug-in groove 110 is opened on the side wall of the carbon block substrate 100 away from the protrusion 200, and the first plug-in groove 110 is similar to the shape of the protrusion 200 and is opened correspondingly.

[0052] Two limit blocks 300 are provided and are integrally arranged on the side wall of the carbon block substrate 100 away from the protrusion 200, and are respectively located on both sides of the width direction of the first plug-in groove 110. A hook portion 310 is formed on the side walls of the two limit blocks 300 that are close to each other. The vertical cross-section of the hook portion 310 is serrated. A groove 120 is provided at one end of the carbon block substrate 100 away from the limit block 300, and grooves 120 are provided on the side walls on both sides of the protrusion. The hook portion 310 can be hooked in the groove 120, and the hook portion 310 and the groove 120 cooperate with each other and are provided with a shallow depth.

[0053] A first locking groove 320 is opened on the side wall of the limit block 300, and a second locking groove is opened on the groove 120. The first locking groove 320 and the second locking groove are connected and opened coaxially. A locking rod 700 is inserted into the first locking groove 320 and the second locking groove. The locking rod 700 is sunk into the first locking groove 320, and the first locking groove 320 is filled and sealed with foam mud.

[0054] The bottom of the first plug-in slot 110 is provided with a second plug-in slot 140, the opening position of the second plug-in slot 140 is coaxial with the opening axis of the carbon block, and the inner wall of the second plug-in slot 140 is provided with a slide groove 150, which is opened along the length direction of the second plug-in slot 140, and there are two slide grooves 150, which are symmetrically opened; two sliders 500 are fixedly connected to the filling block 400, and the two sliders 500 are respectively slidably connected in the two slide grooves 150; the bottom of the second plug-in slot 140 is provided with an annular groove 160 The annular groove 160 is connected with the two slide grooves 150, and the two sliders 500 can slide into the annular groove 160 through the slide groove 150, and can rotate freely in the slide groove 150; the other end of the filling block 400 is integrally provided with a rotating block 600, and the rotating block 600 slides and rotates in the rotating groove 212; the filling block 400, the rotating block 600, and the slider 500 are made of the same material, and the material is the same as that of the carbon block matrix 100, and is formed by molding, and the outer surface of the filling block 400 is roughened to facilitate the adhesion of foam mud.

[0055] The embodiment of the present application also discloses a safe bonding method for bonding anode carbon blocks.

[0056] Reference Figure 2 , a safe bonding method for bonding anode carbon blocks, comprising the following steps:

[0057] Cleaning: Clean the protrusion 200 of the old anode carbon block, clean the carbon bowl 210, and clean the groove 120;

[0058] Specifically, the old anode carbon block is taken out, slowly cooled by heat release at room temperature, or cooled by strong convection through aligned fans. The cooling speed should not be too fast. After it drops to room temperature, the carbon bowl 210 is cleaned to remove surface impurities, and the surface of the connecting protrusion of the old anode carbon block is roughened. Then the groove 120 is cleaned to make a rough surface, and the first plug-in slot 110 and the hook portion 310 of the new anode carbon block are cleaned.

[0059] Hot and cold treatment: cool the old anode carbon block, and then preheat the new anode carbon block to make it expand; the temperature difference between the new anode carbon block and the old anode carbon block is controlled at 200℃-250℃;

[0060] Preparation for bonding: Apply foam mud on the surface of the protrusion 200 of the old anode carbon block, pour foam mud into the second insertion groove 140 and the slide groove 150 of the new anode carbon block, and then insert the filling block 400 and the slider 500 into the second insertion groove 140 and the slide groove 150 of the new anode carbon block respectively; when applying foam mud on the surface of the old anode carbon block, heat the surface, and use gradient heating to gradually reduce the temperature from the protrusion 200 position of the old anode carbon block to the outer edge;

[0061] Specifically, the old anode carbon block is cooled so that the surface temperature of the old anode carbon block is slightly lower than the room temperature, and then the surface of the old anode carbon block connected to the protrusion is preheated. During the preheating, the preheating is carried out from the edge to the middle, and a temperature gradient is formed. The edge temperature during preheating is 100°C-130°C, and the present embodiment is preferably 100°C. The temperature at the protrusion is 150°C-180°C, and the present embodiment is preferably 150°C. The maximum temperature difference does not exceed 50°C. Then, foam mud is applied on the surface of the old anode carbon block, and the surface of the old anode carbon block roughly reaches the coating thickness. The available thickness of the foam mud is 1mm-2mm, and the present embodiment is preferably 1.2mm. When applying the old anode carbon block, the foam mud is pressed so that the foam mud is in full contact with the rough surface, and a certain amount of foam mud is filled in the carbon bowl 210, and the foam mud does not exceed the carbon bowl. 210 one third of the depth; the new anode carbon block is heated as a whole, so that the temperature of the new anode carbon block is higher than that of the old anode carbon block, and the difference with the lowest temperature of the old anode carbon block is 200℃-250℃, and the temperature can be selected according to the material of the foam mud. In this embodiment, it is preferably 300℃, and then a thin layer of foam mud is applied to the first plug-in groove 110 and the hook portion 310 of the new anode carbon block, and then the slide groove 150 and the second plug-in groove 140 are filled with half of the foam mud, and then the filling block 400 is plugged into the second plug-in groove 140, so that the slider 500 slides along the slide groove 150 to the annular groove 160; wherein the foam mud is based on a conventional foam mud formula, with graphite powder partially or completely replacing coke powder, and then 1-3% of aluminum powder is added to obtain a high-conductivity electrolytic aluminum carbon block bonding foam mud.

[0062] Seam alignment: the first insertion groove 110 of the new anode carbon block is inserted into the protrusion 200 of the old anode carbon block, and the hooking portion 310 of the limiting block 300 of the new anode carbon block is hooked into the groove 120 of the old anode carbon block;

[0063] Specifically, the new anode carbon block is placed close to the old anode carbon block so that the filling block 400 and the rotating block 600 are respectively inserted into the connecting groove 211 and the rotating groove 212 of the carbon bowl 210. As the two anode carbon blocks approach each other, the rotating block 600 drives the filling block 400 to rotate, and the filling block 400 drives the sliding block 500 to rotate in the annular groove 160 until the hook portion 310 and the groove 120 are hooked. At this time, the foam mud is squeezed out, and the protrusion of the old anode carbon block is inserted into the first insertion groove 110 of the new anode carbon block.

[0064] Seam filling treatment: filling the connection groove 211 and the first plug-in groove 110 with foam mud or anode carbon block mixed raw materials through the filling hole 130;

[0065] Specifically, after the seaming is completed, foam mud or a mixed raw material of the anode carbon block in a molten state is poured into the connecting groove 211 and the first plug-in groove 110 through the filling hole 130 until the foam mud is squeezed out of the filling hole 130 and the seam.

[0066] Seam pressing treatment: squeeze the old anode carbon block and the new anode carbon block close to each other to make them bond;

[0067] Specifically, the old anode carbon block and the new anode carbon block are squeezed by the device to compress the joint and squeeze out the foam mud, and then the locking rod 700 is inserted into the first locking groove 320 and the second locking groove, and the squeezed foam mud is scraped off.

[0068] Pre-heating treatment: Use a clamp to squeeze the two ends of the joint between the old anode carbon block and the new anode carbon block, and then pre-heat the temperature so that the temperature difference between the new anode carbon block and the old anode carbon block is less than 30℃-50℃;

[0069] Specifically, after the extruded foaming mud is scraped off, a splint is applied to the outer surface of the new anode carbon block and the old anode carbon block, and then pre-heating is performed to heat the old anode carbon block and the new anode carbon block so that the maximum difference between the two does not exceed 50°C. When heating, the old anode carbon block is first heated so that the temperature is close to that of the new anode carbon block, and then the temperature is heated to a temperature exceeding the temperature of the new anode carbon block when the seam is butted, and the temperature does not exceed 80°C when the seam is butted; the fluidity of the foaming mud is initially restricted to reduce the outflow of the foaming mud from the butt joint and reduce the formation of protrusions 200.

[0070] Sintering treatment: Sinter the connected new anode carbon blocks and old anode carbon blocks to form a stable structure.

[0071] Specifically, the initially sintered new anode carbon blocks and the old anode carbon blocks are placed in a sintering furnace for sintering. During sintering, the temperature is selected according to the thickness of the foam mud. The conductivity of the foam mud after sintering is higher than that of the anode carbon blocks.

[0072] The implementation principle of a safe bonding method for an adhesive anode carbon block in an embodiment of the present application is as follows: first, the old anode carbon block is cleaned, and then the old anode carbon block and the new anode carbon block are cooled and heated respectively, and foam mud is coated on their surfaces, and then the filling block 400 is installed, and the seam is processed to make the old anode carbon block and the new anode carbon block close to each other, so that the filling block 400 rotates, and the slider 500 enters the annular groove 160. At this time, the hook portion 310 and the groove 120 are hooked, and then the seam is filled through the filling hole 130, and then the extrusion is continued to squeeze out the foam mud, and then it is preheated and sintered.

[0073] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A bonded anode carbon block, characterized in that: include: The carbon block base (100) is arranged in a cubic shape, and a first insertion groove (110) is provided on the side wall; The protrusion (200) is arranged on a side wall of the carbon block base (100) away from the first insertion groove (110), and is provided with a connection groove (211) to form a carbon bowl (210), and can be inserted into the first insertion groove (110) of another anode carbon block, and grooves (120) are provided on the side walls on both sides of the protrusion (200); The limiting blocks (300) are arranged on the side wall of the carbon block substrate (100) away from the protrusion (200), and two of them are arranged, respectively located on both sides of the first plug-in slot (110), and hooking portions (310) are formed on the side walls of the two limiting blocks (300) close to each other, and the hooking portions (310) can be hooked into the groove (120) of another anode carbon block; the vertical cross-section of the hooking portions (310) is sawtooth-shaped, and the hooking portions (310) and the groove (120) cooperate with each other; A filling block (400) matched with the shape of the connection groove (211) and used to fill the charcoal bowl (210) during bonding; A rotating groove (212) is provided in the connecting groove (211), and the rotating groove (212) is spirally provided along the axis of the connecting groove (211); a second plugging groove (140) is provided at the bottom of the first plugging groove (110), a sliding groove (150) is provided on the side wall of the second plugging groove (140), and an annular groove (160) is provided at the bottom of the second plugging groove (140), and the sliding groove (150) is connected to the annular groove (160); a sliding block (500) is provided on the filling block (400), and the sliding block (500) slides along the sliding groove (150) and enters the annular groove (160).

2. The bonded anode carbon block according to claim 1, characterized in that: A filling hole (130) is provided on the side wall of the carbon block substrate (100); the filling hole (130) is communicated with the first insertion groove (110) and corresponds to the connection groove (211).

3. The bonded anode carbon block according to claim 1 or 2, characterized in that: A first locking groove (320) is provided on the side wall of the limit block (300), the first locking groove (320) is communicated with the groove (120), and a second locking groove is provided on the groove (120), and a locking rod (700) is inserted into both the first locking groove (320) and the second locking groove.

4. A safe bonding method for bonding anode carbon blocks according to any one of claims 1 to 3, characterized in that: The following steps are involved: Cleaning: clean the protrusions of the old anode carbon block, clean the carbon bowl, and clean the grooves; Bonding preparation: Apply foam mud on the raised surface of the old anode carbon block, pour foam mud into the second insertion groove and the slide groove of the new anode carbon block, and then insert the filling block and the slider into the second insertion groove and the slide groove of the new anode carbon block respectively; Seam treatment: plug the first plug-in groove of the new anode carbon block into the protrusion of the old anode carbon block, and hook the hook part of the limit block of the new anode carbon block into the groove of the old anode carbon block; Seam pressing treatment: squeeze the old anode carbon block and the new anode carbon block close to each other to make them bond; Sintering treatment: Sinter the connected new anode carbon blocks and old anode carbon blocks to form a stable structure.

5. The method for safely bonding anode carbon blocks according to claim 4, characterized in that: A cold and hot treatment step is also provided before the bonding preparation step; Hot and cold treatment: cool the old anode carbon block and then preheat the new anode carbon block to make it expand.

6. The method for safely bonding anode carbon blocks according to claim 4, characterized in that: After the seam-aligning step, a seam-filling step is also provided; Seam filling treatment: fill the connection groove and the first plug-in groove with foam mud or anode carbon block mixed raw materials through the filling hole.

7. The method for safely bonding anode carbon blocks according to claim 4, characterized in that: In the hot and cold treatment steps, the temperature difference between the new anode carbon block and the old anode carbon block is controlled at 200°C-250°C.

8. The method for safely bonding anode carbon blocks according to claim 4, characterized in that: After the seam pressing step, a pre-heating step is also provided; Pre-heating treatment: Use a clamp to squeeze the two ends of the connection seam between the old anode carbon block and the new anode carbon block, and then pre-heat the temperature so that the temperature difference between the new anode carbon block and the old anode carbon block is less than 30℃-50℃.

9. The method for safely bonding anode carbon blocks according to any one of claims 4 to 8, characterized in that: In the bonding preparation step, when the foam mud is applied to the surface of the old anode carbon block, the surface is heated, and gradient heating is adopted during heating to gradually reduce the temperature from the protruding position of the old anode carbon block toward the outer edge.

Citation Information

Patent Citations

  • A method for bonding continuously prebaked anode carbon blocks

    CN109913905B

  • Anode carbon block structure for prebaking aluminum cell with no residue anode

    CN105543894A

  • Novel anode carbon block for continuous prebaking

    CN113957486A